Time-domain modelling of interconnects with highly oscillatory sources. Issue 1 (2nd January 2018) - Condon, Marissa; Iserles, Arieh
Abstract : Purpose: This paper aims to explore a new approach for time-domain modelling of interconnects with highly oscillatory modulated sources. Design/methodology/approach: The paper uses an asymptotic method in conjunction with the Green's function of the telegrapher's equations. The Green's function is expressed as a series of rational functions in the Laplace domain and are converted to pole-residue form, thereby enabling time-domain implementation. Findings: The results indicate that the method is accurate for modelling interconnects when wide-varying frequencies are present in the sources. Originality/value: The technique is important in circuit design for assessing signal integrity and in electromagnetic compatibility testing.